Evaluation of the BD Phoenix Automated Microbiology System for Identification and Antimicrobial Susceptibility Testing of Enterobacteriaceae - Carroll, Karen C. (American Society for Microbiology, 2006)
We evaluated the accuracy of the BD Phoenix system for the identification (ID) and antimicrobial susceptibility testing (AST) of 251 isolates of the family Enterobacteriaceae representing 31 species. Organisms were inoculated onto the Phoenix panel according to the manufacturer's instructions. The results from conventional biochemical tests were used for the reference method for ID. Agar dilution, performed according to the CLSI guidelines, was the reference AST method. Essential and categorical agreements were determined. The overall levels of agreement for the genus- and species-level identifications were 95.6% and 94.4%, respectively. Fourteen isolates were incorrectly identified by the Phoenix system; 10 of these were incorrectly identified to the species level. Three of these were Enterobacter (Pantoea) species and four of these were Shigella spp. misidentified as Escherichia coli. For AST results, the essential and categorical agreements were 98.7% and 97.9%, respectively. The very major error, major error, and minor error rates were 0.38%, 0.33%, and 1.8%, respectively. Six isolates (three E. coli isolates and three Klebsiella isolates) were extended-spectrum β-lactamase producers. All six were flagged by the Phoenix system expert rules. The Phoenix system compares favorably to traditional methods for ID and AST of Enterobacteriaceae.